Enhanced Activity of Genes Associated With Photosynthesis, Phytohormone Metabolism and Cell Wall Synthesis Is Involved in Gibberellin-Mediated Sugarcane Internode Growth - Chen, Rongfa; Fan, Yegeng; Yan, Haifeng; Zhou, Huiwen; Zhou, Zhongfeng; Weng, Mengling; Huang, Xing; Lakshmanan, Prakash; Li, Yangrui; Qiu, Lihang; Wu, Jianming (Frontiers in Genetics, 2020)
Internode elongation is an important trait in sugarcane as it affects the sugarcane yield. Gibberellin (GA) is a key modulator of internode elongation in sugarcane. Understanding the gene expression features of GA-mediated internode elongation has both scientific and practical significance. Herein, to understand the transcriptomic changes in internode elongation of sugarcane following GA treatment, 18 cDNA libraries from the internode tissues on days of 0, 3 and 6 in control and GA treatment group were sequenced and their gene expression were studied. RNA-seq analysis revealed 1,338,723,248 reads and 70,821 unigenes from elongating internodes of sugarcane. Comparative studies discovered a large number of transcripts that were differentially expressed in GA-treated samples compared to control. Further analysis revealed that the differentially expressed genes were enriched in the metabolic process, one-carbon compound transport and single-organism process. KEGG pathway annotation showed significant enrichment in photosynthesis and plant hormone signal transduction, indicating its involvement in internode elongation. The function analysis suggested that metabolic pathways and biosynthesis of secondary metabolites, plant hormones and cell wall components were enriched in the internodes of GA-treated plants. The hub genes were identified, with the function of cellulose synthesis. The results of this study provide a global view of mRNA changes during sugarcane internode elongation, and extend our knowledge of GA-mediated cellular processes involved in sugarcane stem growth.